Hot processed beef--microbiological characteristics - Lee, C.Y.; Kastner, Curtis L.; Dikeman, Michael E.; Hunt, Melvin C.; Kropf, Donald H.; Lyon, M.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station, 2011)
To help insure that hot-processed beef has an acceptable shelf life and is microbiologically safe, the microbial characteristics of the product must be evaluated. This is particularly true for hot-processed cuts that are packaged and boxed prior to complete chilling--a practice that facilitates handling. An adequate chilling rate the first several hours postmortem is extremely important to the microbiological quality and shelf life of meat. Therefore, in order to insure an acceptable hot-processed beef product, this study was designed to establish chilling rates necessary to satisfactorily control microbial activity in hot-boned beef.
Keywords: Beef; Hot-processed beef; Microbiological quality; Shelf life